Pembentukan Karakter Siswa dengan Inovasi Pembelajaran Seni Rupa di SMP Islam Pacet - Firdaus, Angga Eriksa; Djatmiko, Budi (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to explore how innovative fine arts learning at Pacet Islamic Middle School contributes to the formation of student character. Through a qualitative approach, in-depth interviews were conducted with students, teachers and school principals to gain a comprehensive understanding of the impact of fine arts learning on student character. The research results show that fine arts learning not only increases students' creativity but also has a positive impact on their emotional control, discipline and sense of responsibility. Students feel more comfortable and are able to manage their emotions better through fine arts activities, while teachers state that students' enthusiasm for this learning motivates them to continue to innovate, although there are still challenges in terms of reference support and training. School principals recognize the importance of character development for teachers as a prerequisite for effectively forming student character. Overall, innovation in fine arts learning at Pacet Islamic Middle School has shown great potential in supporting student character formation, which is supported by the school's commitment to continue developing this program through ongoing training and support.